Determinan Kinerja Karyawan Muslim Pada Lembaga Keuangan Syariah - Intan Dwi Sulistyowati; Sutianingsih Sutianingsih; Ruli Widyaningtyas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Realizing the importance of improving the performance of employees who are members of sharia financial institutions, it is necessary to identify the factors that can influence it. According to studies from previous research, innovative ability, Islamic leadership and personality are factors that can improve the performance of Muslim employees, especially among employees of sharia financial institutions. This theoretical review aims to conduct a study on the influence of Islamic leadership, personality and innovative abilities on the performance of Muslim employees in Islamic financial institutions. Apart from that, it also aims to understand several indicators of these variables which can be used as references in further research. Based on the results of Islamic leadership studies, innovative abilities and employee personality have a significant influence on employee performance in Islamic financial institutions.